Virulensi Beberapa Isolat Metarhizium anisopliae Terhadap Telur Spodoptera frugiperda J. E. Smith (Lepidoptera: Noctuidae): Virulence of Various Isolates of Metarhizium anisopliae Against the Eggs of Spodoptera frugiperda J. E. Smith (Lepidoptera: Noctuidae) - aprilia, Puja; Trizelia; Reflinaldon (DINAMIKA PERTANIAN, 2026)
Background: Spodoptera frugiperda is a pest that causes damage and economic losses to corn plants. One of the biological agents that can be used to control S. frugiperda is the entomopathogenic fungus Metarhizium anisopliae. Objective: This study aimed to determine the most virulent isolate of M. anisopliae against S. frugiperda eggs and to evaluate its effect on larval development. Methods: This study used an experimental method with a Completely Randomized Design (CRD) consisting of 5 treatments and 5 replications. The treatments were (A) M. anisopliae C5IA, (B) M. anisopliae SRJ, (C) M. anisopliae 3B, (D) M. anisopliae Metatek, and (E) control (without fungal treatment). The conidial density used was 10⁸ conidia/ml. The fungus was applied to egg masses of S. frugiperda using a spraying method. The parameters observed were percentage of unhatched eggs, mortality of first instar larvae, percentage of pupae formed, and percentage of adults formed. Data were analyzed using analysis of variance (ANOVA) followed by LSD test at the 5% significance level. Results: All tested isolates of the entomopathogenic fungus M. anisopliae caused egg mortality and affected the life development of S. frugiperda. The percentage of unhatched eggs ranged from 41.92% to 92.00%. The most virulent isolate was M. anisopliae 3B, which was able to control eggs with an unhatched egg percentage of up to 92.00% Conclusions: The isolate M. anisopliae 3B was the most virulent isolate against eggs of S. frugiperda and has potential to be developed as a biological control agent for fall armyworm management.